PENGARUH MENGUNYAH PERMEN KARET TERHADAP PERISTALTIK USUS PASIEN POST APPENDIKTOMI - Grace Erlyn Damayanti S; Arfah May Syara (Jurnal Penelitian Keperawatan Medik, 2018)
In the recovery period, the post appendicectomy intestinal peristalsis had not been reactivated normally. Because of these conditions, patients are advised not to eat and drink first for some time until the intestine activation back to normal. It is often complained by postoperative patients. In addition, surgery on the abdominal organs was no exception appendiktomy may caused paralytic ileus. This condition could inhibited or stopped the work of the intestine, cause pain, nausea, abdominal distension, and the patient must be hospitalized longer. Therefore action were needed that could accelerated the return of the patient's intestinal peristalsis. One of the interventions that could be done was to chew gum. This research was a quasi-experimental design with pre-test and post-test and use data analysis with paired sample t test to test the entire population of post appendictomy patients in Grandmed Hospital of Lubuk Pakam. Sampling using total sampling with a significant level of 95% (p≤0,05). The results of this study indicate that there was effect of chewing gum on the peristalsis intestine of post appendictomy patients with p value 0.000. This suggests that there is the effect of chewing gum on the peristalsis intestine patients appendiktomi appendiktomi can improved the peristalsis intestine of post appendictomy patients in Grandmed Hospital of Lubuk Pakam. Based on the results of the study is expected to hospital and nurse to be able to make chewing gum into one of the interventions to accelerate the return of intestinal peristaltic post appendictomy patient.